A Case of Cryobiopsy of a Large Allergic Bronchopulmonary Aspergillosis‐Associated Mucus Plug - Yusuke Nakamura; Yuto Goto; Nobuhiko Tsukada; Azusa Tsukada; Nobuhiko Uchida; Nana Yazawa; Yasuo Shimizu; Seiji Niho (Respirology Case Reports)
ABSTRACT A 68‐year‐old woman presented with cough and dyspnoea. She was diagnosed with allergic bronchopulmonary aspergillosis with mucus plugs. Forceps biopsy failed to remove a large plug, but cryobiopsy with a 2.4 mm cryoprobe was successful. This case demonstrates that even large mucus plugs can be removed by cryobiopsy.